De novo intracerebral arteriovenous malformations and a review of the theories of their formation. (4th May 2018) - Dalton, A.; Dobson, G.; Prasad, M.; Mukerji, N.
Abstract: Purpose: Arteriovenous malformations (AVM) are still frequently described as congenital lesions in medical texts despite little evidence existing for their congenital nature. Increasing numbers of case reports of de novo AVMs add weight to the notion that they are dynamic lesions and that they can form postnatally. A thorough review of all reported cases of de novo AVM formation and a review of articles relating to AVM pathogenesis was planned to summarise current research on AVM pathogenesis and provide insight into the future implications for AVM research and treatment. Methods and Results: MEDLINE was searched to find 29 cases of de novo AVM formation with prior MRI imaging, nine of which also had prior digital subtraction angiography. A discussion of AVM pathogenesis is undertaken through a review of articles relating to AVM embryology, postnatal angiogenesis, syndromic forms of AVMs and studies of AVM molecular biology and genetics in human and animal models. Conclusions: There is little evidence for an embryological origin through dysregulated vasculogenesis, whereas there is a raft of evidence to support dysregulated angiogenesis in childhood or even adulthood. Translational implications include risk stratification by biomarkers for predicting haemorrhage and novel therapeutic approaches to suppress AVM proliferation and initiate reversal.